2014
DOI: 10.4314/njbas.v21i3.8
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Assessment of the Genetic Variability among 53 Accessions of West African okra [<i>Abelmoschus caillei</i> (A. Chev.) Stevels] from South Western Nigeria

Abstract: Genetic variability in fifty three accessions of West African Okra [Abelmoschus caillei (A. Chev.) Stevels] were evaluated using morphological traits. These accessions were collected from home gardens, seed stores and distant farms in South Western Nigeria and trials carried out in the experimental garden, University of Benin, Nigeria. The primary data on quantitative and qualitative characters collected were subjected to multivariate analyses to determine their relationship and distinctiveness. At P < 0.05, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 20 publications
4
6
0
Order By: Relevance
“…This suggests that genotypes of the same origin that are included in different clusters is an indication of the broad genetic base of the genotypes belonging to the origin. Prasad et al (2001) reported similar results when they studied 60 inbred lines of cucumber and Osawaru et al (2013) in their genetic variability study among 53 accessions of West African okra (Abelmoschus caillei [A.…”
Section: Cluster Analysissupporting
confidence: 52%
“…This suggests that genotypes of the same origin that are included in different clusters is an indication of the broad genetic base of the genotypes belonging to the origin. Prasad et al (2001) reported similar results when they studied 60 inbred lines of cucumber and Osawaru et al (2013) in their genetic variability study among 53 accessions of West African okra (Abelmoschus caillei [A.…”
Section: Cluster Analysissupporting
confidence: 52%
“…It has been stated that genetic affinity between accessions from different regions could be attributed to selection and exchange of germplasm between farmers and ethnic groups [15]. Variability recorded in this study also agrees with the findings of [16], who reported high variability among fifty three okra accessions studied in Nigeria which might be due to genetic drift and selection in different environment.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies used principal coordinates to demonstrate the divergence between genotypes using molecular data (Aitken et al, 2018;El-Esawi et al, 2018;Guzmán, Segura, Aradhya, & Potter, 2018;Taglioti et al, 2018;Wu et al, 2018;Ferreira et al, 2016;Zaher et al, 2011;Van Inghelandt, Melchinger, Lebreton, & Stich, 2010). Other studies were based on principal component analyses (Muller et al, 2018;Valcárcel, Peiró, Pérez-de-Castro, & Díez, 2018;Osawaru, Ogwu, & Dania-Ogbe, 2013;Santi et al, 2012;Jombart, Devillard, & Balloux, 2010). Additionally, studies have been conducted that used the projection of distance technique in a two or three-dimensional plane (Nicky, Carvalho, Assis, & Carvalho, 2008;Sant'Anna & Cruz, 2015).…”
Section: Introductionmentioning
confidence: 99%